Systematic Literature Review: Analysis Of Middle School Students' Difficulties In Solving Integer Problems - Miftahudin, Rifqi Aulia; Putra, Harry Dwi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Middle school students often encounter dificulties in solving integer operation problems, such as understanding concepts like positive and negative integers and correctly applying arithmetic symbols. This study utilizes a Systematic Literature Review (SLR) approach to analyze these difficulties, searching academic databases like Google Scholar, ResearchGate, and Sinta for relevant articles published from 2019 to 2023 and included articles published in 2024 . Articles were selected based on criteria assessing their relevance to the research topic, methodological rigor, and contribution to understanding students' struggles in integer operations. The research identifies three main difficulties: conceptual comprehension, handling factual knowledge, and procedural application. Many students struggle with applying learned concepts, differentiating between positive and negative integers, and using arithmetic symbols accurately. Factors contributing to these difficulties include a lack of seriousness in problem-solving, reliance on peers for answers, and hesitancy in seeking assistance from teachers. The study recommends reinforcing fundamental concepts through diverse teaching methods, fostering student independence in mathematical problem-solving, and developing critical thinking skills to support students in overcoming these challenges and improving their mathematical proficiency.